contestada

If h(x) = x – 7 and g(x) = x2, which expression is equivalent to (g circle h) (5)?

Respuesta :

Answer:

4

Step-by-step explanation:

[tex]h(x)=x-7 \\\\g(x)=x^2 \\\\(g\circ h)(5)= (5-7)^2=(-2)^2=4[/tex]

Hope this helps!

Using composite functions, it is found that the equivalent expression at x = 5 is given by:

[tex](g \circ h)(5) = 4[/tex]

What is a composite function?

A composite function is when a function is used as an input to another function, hence, that is:

[tex](g \circ h)(x) = g(h(x))[/tex].

In this problem, we have that the functions are given as follows:

  • h(x) = x - 7.
  • g(x) = x².

Then, the composite function is given by:

[tex](g \circ h)(x) = g(h(x)) = g(x - 7) = (x - 7)^2[/tex].

We want to find the value of the composite function at x = 5,  hence we have that:

(5 - 7)² = 4.

More can be learned about composite functions at https://brainly.com/question/17684028

#SPJ2